The Influence of Work Environment and Workload on Employee Performance in The Department Of Population and Civil Registration of the Province West Papua with Job Satisfaction as a Mediation Variable - Jecybel Dyana Verent SUILA; Ni Luh Putu INDIANI; I Made Suniastha AMERTA AMERTA (PT Keberlanjutan Strategis Indonesia, 2025)
The existence and advancement of organizations, whether in the public or private sector, relies heavily on the strategic role of Human Resources (HR) as the main driving force. This study aims to analyze the effect of Work Environment and Workload on Employee Performance, with Job Satisfaction as a mediating variable, at the Population and Civil Registration Office of West Papua Province. A quantitative approach was employed, with a total population of 39 employees from the Secretariat Division. The sampling technique used was saturated sampling, where all members of the population were included as samples. Data analysis was conducted using Structural Equation Modeling with the Partial Least Square (SEM-PLS) method. The results show that the Work Environment has a positive and significant effect on both Employee Performance and Job Satisfaction. Workload has a negative and insignificant effect on Employee Performance, but a negative and significant effect on Job Satisfaction. Furthermore, Job Satisfaction has a positive and significant effect on Employee Performance. The mediation analysis reveals that Job Satisfaction partially mediates the effect of the Work Environment on Employee Performance, but does not mediate the effect of Workload on Employee Performance.